2001
DOI: 10.1161/hc4101.097525
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Endothelial Nitric Oxide Biosynthesis in Healthy Smokers With Impaired Endothelium-Dependent Vasodilatation

Abstract: Background-The mechanisms involved in the dysfunction of both endothelium-dependent vasodilatation (EDV) and NO biosynthesis related to smoking are unclear. In this study, EDV was assessed in healthy smokers and nonsmokers in vivo and, using serum from the same individuals, was related to the NO biosynthetic pathway in vitro. Methods and Results-Flow-mediated EDV of the brachial artery was measured in 23 male patients (8 nonsmokers and 15 smokers). Serum was collected, added to confluent (Ϸ85%) monolayers of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
194
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(211 citation statements)
references
References 28 publications
16
194
0
1
Order By: Relevance
“…It was reported that smoking decreases activity of eNOS and may modify the relationship between polymorphisms and expression levels. 20,21 For that reason, we performed multiple binary regression analysis (Table 4). Although smoking was a more powerful risk factor than 27-bp repeat polymorphism in total FHON patients, 4a allele was the only variable with statistical significance after adjustment of the effect of smoking in idiopathic group (p c ¼ 0.026, OR 4.302, 95% CI 1.359-13.621).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that smoking decreases activity of eNOS and may modify the relationship between polymorphisms and expression levels. 20,21 For that reason, we performed multiple binary regression analysis (Table 4). Although smoking was a more powerful risk factor than 27-bp repeat polymorphism in total FHON patients, 4a allele was the only variable with statistical significance after adjustment of the effect of smoking in idiopathic group (p c ¼ 0.026, OR 4.302, 95% CI 1.359-13.621).…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that there was more smoker and higher exposure to smoking in FHON patients compared to controls. It was previously reported that smoking reduces the function of eNOS 20,37,38 and is a potential risk factor of the development of FHON and LeggCalve-Perthes disease. 8,18,24,[39][40][41] The results previous studies are compatible with our speculation.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] However, the majority of in vitro data has involved the use of cigarette smoke extract solution, which is probably not an appropriate physiological model, as circulating particulate of cigarette smoke has to first bypass the lung. 40 Thus, the effect of smoking on the NO pathway seems to be more complex on a cellular level than suggested by the described Abbreviations: ALT, alanine transaminase; ANOVA, analysis of variance; AST, aspartate aminotransferase; BMI, body mass index; BP, blood pressure; CRP, C-reactive protein; eGFR, estimated glomerular filtration rate; g-GTP, g-glutamyl transpeptidase; HbA1c, hemoglobin A1c; HDL-c, high-density lipoprotein-cholesterol; HOMA, homeostatic model assessment; LDL-c, low-density lipoprotein-cholesterol; NS, nonsignificant. Data are shown as mean ± s.e.…”
Section: Discussionmentioning
confidence: 99%
“…25 Human endothelial cells exposed to sera from smokers have decreased nitric oxide availability despite increased nitric oxide synthase expression, with scavenging of nitric oxide by increased reactive oxygen species generation. 26,27 Smokingassociated endothelial dysfunction can be ameliorated by 3-hydroxy-3-methylglutaryl (HMG)-coenzyme A (CoA) reductase inhibitor therapy independently of changes in lipid levels, 28 by supplementation with tetrahydrobiopterin, 26 and by xanthine oxidase inhibition with allopurinol. 29 Monocytes isolated from smokers demonstrate increased adherence to endothelial cells, which is corrected by vitamin C therapy.…”
Section: Smoking-related Vascular Inflammation and Oxidative Stressmentioning
confidence: 99%